Moral judgment competence of midwifery students and its influencing factors: a cross-sectional study - Hu, Juan; Fan, Min; Ding, Hui; Chen, Xi (Frontiers in Public Health, 2025)
BackgroundMidwives frequently encounter complex ethical dilemmas in clinical practice, underscoring the need for strong moral judgment competence. However, limited research has investigated this competence among midwifery students in China.ObjectivesThis study aimed to assess the level of moral judgment competence among Chinese midwifery students, examine its relationship with empathy, and identify influencing factors.MethodsA cross-sectional study was conducted with 213 midwifery students from three vocational colleges in Hunan Province, China. Data were collected using the Chinese versions of the Moral Judgment Test (MJT) and the Jefferson Scale of Empathy for Nursing Students (JSE-NS), along with demographic information. Statistical analyses included Pearson’s correlation and multiple linear regression.ResultsThe mean MJT score was 11.81 ± 7.48, indicating a moderate level of moral judgment competence. Empathy also reached a moderate level (87.17 ± 12.90), and a significant positive correlation was found between empathy and moral judgment competence (r = 0.502, p < 0.01). Multiple linear regression identified five significant predictors: year of study, only-child status, religious affiliation, prior experience in studying nursing ethics, and empathy level, collectively explaining 37.5% of the variance in moral judgment competence (F = 22.219, p < 0.05, adjusted R2 = 0.375).ConclusionThis study provides the first empirical evidence on moral judgment competence among Chinese midwifery students. The findings highlight the importance of integrating empathy cultivation and ethics education into midwifery training. Targeted, individualized teaching strategies may be effective in enhancing students’ ethical reasoning and preparing them for future clinical challenges.